Veintisiete años de seguimiento de las clínicas integrales de la Facultad de Odontología de la Universidad de Antioquia (1970-1996)- Parte I- índices y demás instrumentos evaluativos utilizados - Mejía-Villa, Raúl; Yepes-D., Fanny Lucía (Revista Facultad de Odontología Universidad de Antioquia, 2016)
The present retrospective study analyzes the processes implemented by the dental school of the Antioquia University to help the senior dental students fulfill the teaching objetives of the 9th and 10th semester dental clinics. For this purpose, the dental charts of the patients in the 9th and 10th semester clinics were used. The variables that were studied include treatment and other procedures perfomed on the patient, the degree of efficiency and efficacy of these procedures, and the patients’ quality of service. These variables were analyzed beyond the clinical-pathological perspective, to determine the cualitadve aspects of treatment, such as the execution of "preventive treatment approaches", the efficiency of the working environment, and patient respect. Administrative procedures were also analyzed. These include handling of dental charts and files, availability of teaching and assisting resources, equipment, instruments, and infrastructure that could affect the efficiency and efficacy of de service to the patient, and the student’s attitude in the clinic. In order to evaluate the results, several medical service indexes and measurement instruments were adapted to the present study, since the existing dental indexes lacked the specific indicators needed for the purpose of this study. The description and instructions for the use of these indexes are presented. The results show that the efficiency and efficacy of the procedures is low, and the cuality* and continuity of treatment .115 poor. The reason for these findings is that the goals set by the institution have lead towards viewing and utilizing the patient primarily as a means for learning, where the quality of service to the patient is undermined. The results of this study will be presented in three separate publications as follows: I. Adapted indexes and measurement instruments II. Evaluation fron 1970 to 1989 III. Evaluation from 1990 to 1996